Imaging analysis 3D cone-beam computed tomography of a suspected infected radicular cyst in the mandible - Damayanti, Merry Annisa; Firman, Ria Noerianingsih; Ramadhan, Fahri Reza; Rachmawati, Ika; Rahman, Fadhlil Ulum Abdul; Nurrachman, Aga Satria; Sarifah, Norlaila; Ramadhan, Alongsyah Zulkarnaen; Gunawan, Indra (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI); Vol 6 No 3 (2022): Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This article is aimed to report the use of cone-beam computed tomography (CBCT) imaging analysis on a radiolucent lesion case. Case Report: A 24-year-old female patient was referred to dentomaxillofacial radiology installation, at Universitas Padjadjaran Dental Hospital for a CBCT examination of a lower jaw lesion. The CBCT result demonstrated a large radiolucent lesion at the periapical of tooth 37 with a mostly diffuse border that extended posteriorly to the ramus. There was a cortical thinning on the lingual side alveolar bone. Density analysis revealed an average density of –22,9 grayscale. Conclusion: CBCT 3D could analyze lesions from qualitative and quantitative approaches. Based on these approaches, the lesion of this case led to a suspect of infected radicular cyst.